2014
DOI: 10.1021/am506766e
|View full text |Cite
|
Sign up to set email alerts
|

Nongassing Long-Lasting Electro-osmotic Pump with Polyaniline-wrapped Aminated Graphene Electrodes

Abstract: An efficient nongassing electro-osmotic pump (EOP) with long-lasting electrodes and exceptionally stable operation is developed by using novel flow-through polyaniline (PANI)-wrapped aminated graphene (NH2-G) electrodes. The NH2-G/PANI electrode combines the excellent oxidation/reduction capacity of PANI with the exceptional conductivity and inertness of NH2-G. The flow rate varies linearly with voltage but is highly dependent on the electrode composition. The flow rates at a potential of 5 V for pristine NH2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 46 publications
2
50
1
1
Order By: Relevance
“…However, the authors reported that water electrolysis still became the dominating Faradaic reaction at increased applied potentials due to the slow reaction rate of oxidation or reduction of PHBQ. Similarly, polyanilinewrapped aminated graphene electrodes were used in combination with a silica frit to produce a long-lasting, non-gassing EOP (Kumar et al 2015). Finally, we have previously shown poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) as an electrode material to mitigate water electrolysis at applied potential as high as 250 V across (rigid) electrokinetic systems (Bengtsson et al 2014;Erlandsson and Robinson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors reported that water electrolysis still became the dominating Faradaic reaction at increased applied potentials due to the slow reaction rate of oxidation or reduction of PHBQ. Similarly, polyanilinewrapped aminated graphene electrodes were used in combination with a silica frit to produce a long-lasting, non-gassing EOP (Kumar et al 2015). Finally, we have previously shown poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) as an electrode material to mitigate water electrolysis at applied potential as high as 250 V across (rigid) electrokinetic systems (Bengtsson et al 2014;Erlandsson and Robinson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…4 Having a single dominant proton-generating anode reaction and a single dominant proton-consuming cathode reaction balancing the anode reaction such that the net cell reaction is nil, their small (∼0.3 V) flow threshold was defined by the pH difference between the anode and cathode compartments, and their flow was constant for a particular applied voltage or current.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The maximum value of obtained electroosmotic flux was 43 µL/min/cm/V for EPANI‐A, and was higher than 40 µL/min/cm/V obtained for polyanthraquinone based EOP . It was even higher than the EOP assembled with polybenzoquinone/hydroquinone polymers , alizarin dye , ceria , and PANI‐graphene composite electrodes, but lower than the hydrogen ferricyanide and Ag/Ag 2 O electrodes . The lower performance is associated with the sluggish kinetics of the electrode.…”
Section: Resultsmentioning
confidence: 73%